Vascular Kinin B1 and B2 Receptors Determine Endothelial Dysfunction through Neuronal Nitric Oxide Synthase - Mesquita, Thássio R. R.; Campos-Mota, Gianne P.; Lemos, Virgínia S.; Cruz, Jader S.; de Jesus, Itamar C. G.; Camargo, Enilton A.; Pesquero, Jorge L.; Pesquero, João B.; Capettini, Luciano Dos Santos A.; Lauton-Santos, Sandra (Frontiers in Physiology, 2017)
B1- and B2-kinin receptors are G protein-coupled receptors that play an important role in the vascular function. Therefore, the present study was designed to evaluate the participation of kinin receptors in the acetylcholine (ACh)-induced vascular relaxation, focusing on the protein-protein interaction involving kinin receptors with endothelial and neuronal nitric oxide synthases (eNOS and nNOS). Vascular reactivity, nitric oxide (NO·) and reactive oxygen species (ROS) generation, co-immunoprecipitation were assessed in thoracic aorta from male wild-type (WT), B1- (B1R−/−), B2- (B2R−/−) knockout mice. Some vascular reactivity experiments were also performed in a double kinin receptors knockout mice (B1B2R−/−). For pharmacological studies, selective B1- and B2-kinin receptors antagonists, NOS inhibitors and superoxide dismutase (SOD) mimetic were used. First, we show that B1- and B2-kinin receptors form heteromers with nNOS and eNOS in thoracic aorta. To investigate the functionality of these protein-protein interactions, we took advantage of pharmacological tools and knockout mice. Importantly, our results show that kinin receptors regulate ACh-induced relaxation via nNOS signaling in thoracic aorta with no changes in NO· donor-induced relaxation. Interestingly, B1B2R−/− presented similar level of vascular dysfunction as found in B1R−/− or B2R−/− mice. In accordance, aortic rings from B1R−/− or B2R−/− mice exhibit decreased NO· bioavailability and increased superoxide generation compared to WT mice, suggesting the involvement of excessive ROS generation in the endothelial dysfunction of B1R−/− and B2R−/− mice. Alongside, we show that impaired endothelial vasorelaxation induced by ACh in B1R−/− or B2R−/− mice was rescued by the SOD mimetic compound. Taken together, our findings show that B1- and B2-kinin receptors regulate the endothelium-dependent vasodilation of ACh through nNOS activity and indicate that molecular disturbance of short-range interaction between B1- and B2-kinin receptors with nNOS might be involved in the oxidative pathogenesis of endothelial dysfunction.